Construction, characterization and bioactivity evaluation of curcumin nanocrystals with extremely high solubility and dispersion prepared by ultrasound-assisted method - Dan Yang; Lili Wang; Linxuan Zhang; Mengqi Wang; Dan Li; Ning Liu; Dechun Liu; Mouming Zhao; Xiaolin Yao (Ultrasonics Sonochemistry, 2024)
Curcumin (Cur) as a natural pigment and biological component, can be widely used in food and beverages. However, the water insolubility of Cur significantly limits its applications. In this study, we prepared a series of nanocrystals via ultrasound-assisted method to improve the solubility and availability of Cur. The results showed artemisia sphaerocephala krasch polysaccharide (ASKP), gum arabic (GA) and wheat protein (WP) were outstanding stabilizers for nanocryatals except traditional agent, poloxamer 188 (F68). The obtained curcumin nanocrystals (Cur-NC) displayed a rod-shaped, crystal- and nanosized structure, and extremely high loading capacity (more over 80 %, w/w). Compared with raw powder, Cur-NC greatly improved the water solubility and dispersibility, and the slow and complete release of Cur of Cur-NC also endowed them excellent antioxidant capacities even at 10 μg/mL. Importantly, as functional factor additive in beverages (e.g. water and emulsion), Cur-NC could increase the content of Cur to at least 600 μg/mL and retain a good stability. Overall, we provided an effective improvement method for the liposoluble active molecules (e.g. Cur) based on the nanocrystals, which not only tremendously enhanced its water solubility, but also strengthened its bioactivity. Notably, our findings broadened the application of water-insoluble compounds.